(3JgPjH GdCMcGes - (3GdWhSj, CHh LYaQ, fUjQ GdOjf, eMeO Hf eMeO Hf GdMSf, J (B672 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3cJGH GdfcGM , HGH GdSfI aj GdfcGM (B: (3eMeO Hf jYbhH Yf YOO ef CUMGHfG Yf CMeO Hf eMeO Hf CHj aVGd bGd bGd CHh YHO Gddg Ydjg GdSdGe QcYJGf jUdjgeG GdeJRhL CaVd ef SHYjf QcYI jUdjgeG GdCYRH (B...s
(3BNQgG (B:s
... (3Yf CHj YHO Gddg Ydjg GdSdGe Cf KhQG bJd MeGQG Ydi YgO GdfHj Udi Gddg Ydjg hSde aQaY Pdc Edjg hgh aj CfGS ef CUMGHg efge CHh HcQ hYeQ (B.. (3aEf GdKhQ ONd Ydi GdMeGQ aj eSJQGMg (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B7/ 30s
(3GdPQjYI (B4\2263s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs